Melampaui Pelaku: Meninjau Kembali Subjek Hukum dalam Politik Uang Melalui Siyāsah Dustūriyyah dan Peraturan Pemilu Indonesia - Palinrungi, Inda Sari; Dalle, Jumarni; Rasdiana, Rasdiana; Alimuddin, Hardiyanti (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2026)
Money politics remains one of the most persistent electoral violations hindering the realization of democratic, free, and fair elections in Indonesia. Although Indonesia's election laws prescribe criminal sanctions for such practices, the legal construction of criminal liability remains limited to specific categories of offenders. This issue has gained renewed attention following Constitutional Court Decision No. 59/PUU-XXII/2024, which rejected the proposed expansion of the legal subject of money politics offenses on the grounds that such reform falls within the legislature's open legal policy. This study aims to examine the legal subject of money politics under Indonesia's election regulations and to reassess its construction through the perspective of siyasah dusturiyyah. This study employed normative legal research using statutory, conceptual, and case approaches. Primary, secondary, and tertiary legal materials were analyzed qualitatively through a descriptive-analytical method by examining Law No. 7 of 2017 on General Elections alongside its constitutional development through Constitutional Court Decision No. 59/PUU-XXII/2024. The findings indicate that the existing legal framework primarily imposes criminal liability on direct perpetrators and does not comprehensively encompass other actors involved in the chain of money politics, including intermediaries, political beneficiaries, and affiliated parties. Constitutional Court Decision No. 59/PUU-XXII/2024 maintains this legal construction by recognizing the expansion of legal subjects as a matter of legislative policy. From the perspective of siyasah dusturiyyah, however, such limitations do not fully reflect the principles of justice, public welfare, accountability, and constitutional responsibility, as all parties contributing to electoral corruption should be subject to legal accountability. Reformulating Indonesia's election regulations is necessary to broaden the legal subject of money politics beyond direct perpetrators to include all actors contributing to electoral violations. Such reform would strengthen law enforcement, enhance electoral integrity, and promote democratic governance consistent with the principles of siyasah dusturiyyah.